(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In recent years, attention to the study and teaching of foreign languages has increased significantly. To do this, it is necessary to make foreign language lessons, especially English, interesting, that is, use various innovative methods, technical means, and interactive games that attract different students. The use of such games in the classroom increases the student’s interest in learning science. This article describes methods for learning French and English through games.